Singgasana Keraton Ngayogyakarta Hadiningrat dalam Dialektika Universalisme Vs. Partikularisme HAM: (Komentar terhadap Putusan MK 88/PUU-XIV/2016) - Febriansyah Ramadhan; Luthfi Marfungah (Jurnal Hukum Lex Generalis, 2020)
This article will elaborate on the study of women seen from the lens of universalism vs. human rights particularism in Decree No. 88/PUU-XIV/2016. The ruling is about the gender requirements or the necessity to have a wife in charging the Sultan of Yogyakarta. Allegations of discrimination pinned by the petitioners and judges of the Court of Justice against the condition will be the main focus in this study. The main headline or argument built by the petitioners through his power and also the nine judges of the Constitutional Court is "the state must not interfere with the SpecialTy of the Yogyakarta Palace". In the glasses of the applicants, intervention is carried out in the form of arrangements in the KDIY Law that do not give women the opportunity. Though keep in mind, the ratio of the legis of the formation of the rule is because it is based on historical reasons, where the position of the Sultan is always filled by men for decades. So, who exactly intervenes, the law, the way of thinking of judges or petitioners who actually judge the wisdom of the palace with a discriminatory approach based on universal principles? To help answer that question, the study used normative research that will delve into legal materials ranging from legal sources formil and some literature literature. The benefit of this research is to dispel bad precedents in our statehood tradition which often judge matters of local wisdom with an approach to human rights universalism.